2018
DOI: 10.1002/cyto.b.21721
|View full text |Cite
|
Sign up to set email alerts
|

Application of immunophenotypic analysis in distinguishing chronic myelomonocytic leukemia from reactive monocytosis

Abstract: Objectives The purpose of this study was to determine whether immunophenotypic profiles detected by flow cytometry are useful in differentiating chronic myelomonocytic leukemia (CMML) from reactive monocytosis, and between CMML subtypes. Methods Eight‐color flow cytometry was used to immunophenotype blasts, monocytes, and granulocytes in the bone marrow of 34 patients with CMML and 12 patients with reactive monocytosis. Results Bone marrow myeloblast, promonocyte, and monocyte counts by flow cytometry were sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…MDS and MDS/MPN cases showed higher intensity CD117 expression and lower intensity CD38, as compared to Non‐MDS cases. Bright CD117 expression on myeloblasts appeared highly specific for myelodysplasia, with positivity in 12/23 MDS, and 7/8 MDS/MPN and none of the 21 Non‐MDS cases, in line with a number of previous publications (De Smet et al, 2012 ; Feng et al, 2018 ; Matarraz et al, 2008 ; Ogata et al, 2006 ; Stachurski et al, 2008 ). Comparison of lower‐risk MDS (very low/low IPSS‐R scores) to higher‐risk MDS (intermediate/high/very high IPSS‐R scores) showed no statistically significant difference in the intensity of CD117 expression (MFI of 504 ± 225 in lower‐risk versus 589 ± 358 in higher‐risk, p = 0.7074), suggesting that this marker is useful irrespective of the risk score.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…MDS and MDS/MPN cases showed higher intensity CD117 expression and lower intensity CD38, as compared to Non‐MDS cases. Bright CD117 expression on myeloblasts appeared highly specific for myelodysplasia, with positivity in 12/23 MDS, and 7/8 MDS/MPN and none of the 21 Non‐MDS cases, in line with a number of previous publications (De Smet et al, 2012 ; Feng et al, 2018 ; Matarraz et al, 2008 ; Ogata et al, 2006 ; Stachurski et al, 2008 ). Comparison of lower‐risk MDS (very low/low IPSS‐R scores) to higher‐risk MDS (intermediate/high/very high IPSS‐R scores) showed no statistically significant difference in the intensity of CD117 expression (MFI of 504 ± 225 in lower‐risk versus 589 ± 358 in higher‐risk, p = 0.7074), suggesting that this marker is useful irrespective of the risk score.…”
Section: Discussionsupporting
confidence: 87%
“…These abnormalities include myeloblast percentage, frequency of stage‐1 hematogones, myeloblast heterogeneity, and stem cell and myeloblast immunophenotypic aberrancies. Changes in frequency of myeloblasts and hematogones and immunophenotypic aberrancies of myeloblasts have been extensively studied in previous publications (Chen et al, 2020 ; De Smet et al, 2012 ; Della Porta et al, 2012 ; Feng et al, 2018 ; Goardon et al, 2009 ; Kern et al, 2010 ; Kussick et al, 2005 ; Maftoun‐Banankhah et al, 2008 ; Matarraz et al, 2008 ; Ogata et al, 2006 ; Porwit et al, 2014 ; Schenkel et al, 2019 ; Stachurski et al, 2008 ; van de Loosdrecht et al, 2008 ), whereas limited information is available on abnormal blast heterogeneity, changes in relative composition of myeloid progenitors, and frequency of stem cell abnormalities in MDS (Jevremovic et al, 2014 ; Ostendorf et al, 2018 ; Schenkel et al, 2019 ; Toft‐Petersen et al, 2016 ; Will et al, 2012 ). All parameters measured by this approach are quantitative, eliminating the need for extensive expertise in interpretation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For other entities like MDS, the evaluation of monocytes using e.g., CD56 is part of various diagnostic scores [ 52 , 53 ]. In addition, CD56 expression has been described to distinguish clonal monocytes within CMML from reactive monocytosis [ 54 56 ]. These observations have led us to also analyze aberrations outside of the CD34 + CD117 + compartment.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike in most of the acute leukemia cases and in several subgroups of MDS, chronic myelomonocytic leukemia (CMML) remains a disease that may be quite difficult to diagnose since cytogenetic evidence of clonality is found in only 20% to 40% of CMML cases. In the manuscript of Feng et al the authors describe that CMML patients display phenotypic aberrancies not just in monocytes but also in granulocytes, and more frequently in myeloblasts. They found that aberrant expression of two or more antigens in myeloblasts by flow cytometry has a high sensitivity (94.1%) and a high specificity (100%) to differentiate CMML from reactive monocytosis.…”
Section: When Two Diseases Are Quite Alike: Cmml and Reactive Monocytmentioning
confidence: 99%